Modeling of 3D brick-and-mortar structures using cohesive zone finite elements - Hunter, G; Djumas, L; Brassart, L; Molotnikov, A (Wiley, 2024)
Nacre-inspired brick-and-Mortar composite structures exhibit exceptional combinations of properties as well as a highly tuneable mechanical response, due to their large range of design parameters. Understanding the effect of these parameters on the response is essential to optimally design these structures and can be guided by modeling. Traditional models only consider 2D geometries and limited attempts at modeling 3D geometric designs exist. Herein, 3D brick-and-mortar structures using a finite element in conjunction with an experimentally calibrated cohesive zone model to represent the layers are proposed. The model is successfully validated against experimental results for a nonplanar brick assembly using so-called osteomorphic bricks. The capabilities of the model are further demonstrated through a parametric study, where the effect of brick shape, number of bricks, and soft layer material properties on the structure mechanical properties (elastic modulus, yield strength and toughness) are investigated. Numerical results show that toughness is significantly increased by transitioning from a “two-peak” failure mechanism to a “peak-plateau-peak,” which is controlled by the brick shape. It is also shown that 3D structures may exhibit significant out-of-plane deformation involving the cooperative motion of many bricks, which may contribute to their improved toughness compared to 2D structures.